An Analysis of the Effects of Spatial Dependence on Economic Growth Among Regencies and Cities in Java - Khotiawan, Ma'rufa; Sakti, Rachmad Kresna; Wahyudi, Setyo Tri (Muhammadiyah University Press, 2023)
Java is inarguably essential for Indonesia’s economy with its 59% contribution to the country’s GDP. However, behind the tremendous participation lies high regional disparity, poverty, and unemployment, which have become challenges to its economic development. This research aims to analyze the role of spatial dependence on regional economic growth in 119 regencies and cities in Java during the 2015- 2019 period. Exploratory Spatial Data Analysis (ESDA) and Spatial Durbin Model (SDM) were used to analyze the determinants of the spatial dependence and its impact on regional economic growth. The travel time among regions was utilized for the spatial weight matrix. The existence of spatial dependence in inter-regional economic growth can be identified from all models. The positive value of Moran’s I in the ESDA analysis indicates that the spatial pattern of the growth is clustering. The lambda parameter in the SDM estimation indicates the occurrence of backwash spillover in the effect of the spatial dependence on economic growth. The direct effects of initial per capita income, physical capital investment, road infrastructure, population growth, and education are significant on economic growth. Furthermore, the spillover effect of initial per capita income and education is also significant on the inter-regional economic growth.